Wellness among African-American and Caucasian students attending a predominantly White institution. (October 2019) - Oliver, Michael D; Datta, Subimal; Baldwin, Debora R
The wellness movement is growing on college campuses; however, the examination of race is lacking. We examined aspects of physical and emotional well-being as a function of race in 197 college students at a predominantly White institution. Results revealed racial differences on diet, F (1, 196) = 7.537, p  = 0.007 and resilient coping, F (1, 196) = 8.614, p  = 0.004. Furthermore, regression analyses revealed that the association between stress and coping was moderated by race ( F (1, 196) = 8.196, p  = 0.005), demonstrating that Whites and Blacks experience and cope with stressors in differing ways. Findings of this study suggest that race is an influential factor of wellness and subsequent well-being in college students.